Wpływ pierwotnych procedur tworzenia specjalnych stref ekonomicznych w Polsce na efekty funkcjonowania tych stref - Siudak, Przemysław (The Inluence of Primary Procedres Concerning Constituting Special Economic Zones in Poland on the Effects of their Funcioning, 2007)
The article concentrates on discussing the discord, which arose between the procedure of constituting special economic zones expressed in The assumptions of constituting special economic zones in 1996-1997 - the document on programme character and the dominating practice, supported by another programme document - The functioning and constituting special economic zones in Poland. Assumptions on the effects of functioning these zones in Poland. The author also presents the positioning of the reasons for establishing each of the zones with reference to the directives included in the documents mentioned above. The article also discusses general regulations of the bill from the 20th of October 1994 on special economic zones, concerning constituting such zones and the resulting threats in the form of the possibility of losing the initiative by the Minister of Economy as for creating special economic zones in favour of local economic and regional lobbies. The reasons as well as the effects of dispersing special economic zones were pinpointed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 376-386